2016
DOI: 10.1186/s12939-016-0402-0
|View full text |Cite
|
Sign up to set email alerts
|

The effect of childhood and current economic status on depressive symptoms in South Korean individuals: a longitudinal study

Abstract: BackgroundMental health inequality along the economic strata is prominent in South Korea, particularly as intergenerational material transfer is becoming increasingly important in gaining economic status. Therefore, this study aimed to investigate the relationship between current and childhood economic status and depressive symptoms in adults aged 20 or above.MethodsThis study used data from the Korean Welfare Panel Study (KOWEPS), 2010 to 2013. A total of 9,645 individuals aged 20 years or above without depre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 28 publications
2
6
0
Order By: Relevance
“…Using cross-sectional data from 19 European countries in 2014, Boe et al found that younger adults (25–40) who had experienced financial difficulties as children had higher depression scores in adulthood, while older adults (over 40) did not [ 42 ]. A similar association between adverse childhood financial situation and adults’ depression was also found in a longitudinal study [ 47 ]. Based on a national representative sample of 9,645 South Korean adults without depressive symptoms at baseline, Kim, et al found that experiencing financial difficulties in childhood was associated with the increased chance of depression in adulthood [ 47 ].…”
Section: Resultssupporting
confidence: 82%
See 2 more Smart Citations
“…Using cross-sectional data from 19 European countries in 2014, Boe et al found that younger adults (25–40) who had experienced financial difficulties as children had higher depression scores in adulthood, while older adults (over 40) did not [ 42 ]. A similar association between adverse childhood financial situation and adults’ depression was also found in a longitudinal study [ 47 ]. Based on a national representative sample of 9,645 South Korean adults without depressive symptoms at baseline, Kim, et al found that experiencing financial difficulties in childhood was associated with the increased chance of depression in adulthood [ 47 ].…”
Section: Resultssupporting
confidence: 82%
“…The positive and significant association between perceived financial strain in childhood and depression in adults was found in both a cross-sectional study and a longitudinal study [ 42 , 47 ]. Using cross-sectional data from 19 European countries in 2014, Boe et al found that younger adults (25–40) who had experienced financial difficulties as children had higher depression scores in adulthood, while older adults (over 40) did not [ 42 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Lower DASS-21 scores in individuals with higher education levels also support the findings of a previous study, suggesting a lower risk of depressive disorder among well-educated subjects [40]. A large population-based survey in China highlighted that education level influenced depression or anxiety risk [41] albeit the presence of intermediary variables between education and negative percepts, such as occupational factors [42] or discrimination [43]. Subjects with low levels of education potentially have a greater inclination toward anxiety [44] because they may struggle to understand information about the pandemic.…”
Section: Discussionsupporting
confidence: 83%
“…Heflin and Iceland [14] reported a strong relationship between MH, especially when encountering problems with paying bills and having one's phone disconnected, and depression in the U.S. data. In Korea, numerous researchers have reported the association between low socioeconomic status and mental disorders, such as depressive symptoms [15,16] and suicidal ideation [17] and attempts [18]. However, in Korea, onedimensional and conventional income-based measures of socioeconomic status have been much more commonly used than multidimensional measures in studies examining the association between mental disorders and low socioeconomic status.…”
Section: Introductionmentioning
confidence: 99%